Mind the Gap: Discrepancy Between Customer Expectation and Perception on Commercial Chatbots Usage - Chan, Winslet Ting Yan; Leung, Chi Hong (Asian Journal of Empirical Research, 2021)
The advent of artificial intelligence gives rise to chatbots. Chatbots are widely adopted by marketers as query-answering tool to build, manage, and grow customer relationship by responding to customers’ questions in a human-being manner automatically. While the far-reaching potential of chatbots for commercial purposes has been widley recognized by marketers, this study attempts to advance marketers’ understanding on chatbots from the perspective of users – customers. Understanding customer expectation and perception on chatbots usage may help marketers to ensure customer experience consistently meets or exceeds their expectation. The purpose of this study is to find out if there is discrepancy between customer expectation and perception of chatbots performance, what causes the discrepancy, and how to minimize the discrepancy. Specifically, this study investigates the reasons why customers use chatbots, their usage experience, and their attitude towards chatbots in terms of perceived usefulness, perceived ease of use, and perceived helpfulness. Respondents expressed that chatbots are useful and easy to use, yet the responses provided by chatbots are not very accurate and humorous. The findings revealed that respondents expect marketers to improve the chatbots performance in areas of human-like communication and the entertaining features. This study provide marketers with implications on how to design and improve commercial chatbots to close or minimize the gap between customer expectation and experience.